2019
DOI: 10.15171/jlms.2019.44
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Efficacy of Chlorhexidine, Sodium Hypochlorite, the Diode Laser and Saline in Reducing the Microbial Count in Primary Teeth Root Canals – An In Vivo Study

Abstract: Please cite this article as follows: Walia V, Goswami M, Mishra S, Walia N, Sahay D. Comparative evaluation of the efficacy of chlorhexidine, sodium hypochlorite, the diode laser and saline in reducing the microbial count in primary teeth root canals -an in vivo study. Abstract Introduction:One of the primary goals of pulpectomy is to decrease the sum total of microorganisms and disinfect the tooth root canal system. To achieve this, mechanical preparation, irrigation, disinfection and obturation of the root c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 31 publications
2
14
0
4
Order By: Relevance
“…For this study direct irradiation with the fiber tip was placed within the root canal at its working length, and light emission at tip and from the lateral sides, thus leading to even horizontal and vertical light distribution for disinfection. According to Walia et al [23] 980 nm near-infrared diode has antimicrobial action on its own due to laser scattered radiation and photodynamic effects, therefore not just purely relying on the irrigation solution to disinfect the canal space. For this study, clinically near infrared diode laser combines with CHX demonstrated the highest percentage of bacterial kill (>80%) compared to the other treatment groups with over 80% achieved on the external root surface over a 72-hour period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study direct irradiation with the fiber tip was placed within the root canal at its working length, and light emission at tip and from the lateral sides, thus leading to even horizontal and vertical light distribution for disinfection. According to Walia et al [23] 980 nm near-infrared diode has antimicrobial action on its own due to laser scattered radiation and photodynamic effects, therefore not just purely relying on the irrigation solution to disinfect the canal space. For this study, clinically near infrared diode laser combines with CHX demonstrated the highest percentage of bacterial kill (>80%) compared to the other treatment groups with over 80% achieved on the external root surface over a 72-hour period.…”
Section: Discussionmentioning
confidence: 99%
“…Manual agitation of irrigant is recognized to only produce weak fluid movement that is not sufficient to remove bacterial biofilms [22] and hence this corresponds to the lowest percentage of bacterial kill compared to the other treatment groups; achieving less than 30% total kill up to 24 hours. A recent report by Walia et al [23], looked into irrigation solution for pulpectomy in deciduous teeth in which E. faecalis was isolated. The study showed no significant difference between using CHX or sodium hypochlorite, both achieved significant bacterial reduction, hence CHX was chosen for this study as it has fewer complications for clinical use compared to NaOCl or hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, after being cooled, the extract was filtered and held in a refrigerator (4°C) to be used as PPE solution. 12…”
Section: Preparation Of the Pomegranate Peel Extractmentioning
confidence: 99%
“…9 Among the types of lasers, diode lasers have been widely used due to their small size and low price. 10 Diode lasers can easily penetrate into curved canals due to their flexible and small size fibers, 11,12 better distribution of laser light in the root canal system and thus better disinfection of the canal. Diode lasers interfere slightly with water and hydroxyapatite, and enhances its bactericidal effect with thermal photo disruptive activity in inaccessible areas of dentin.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to eradicate the microorganisms and their by products from the root canal and pulp chamber. Some of the more commonly used irrigants during pulpectomy procedure include sodium hypochlorite, chlorhexidine gluconate, Ethylenediamine tetraacetic acid, mixture of tetracycline, acid and detergent, hydrogen peroxide, etc… (Walia et al, 2019) This research study shows promise as newer materials are being created everyday. The reasons for loss of pulp vitality could be attributed to dental caries that invades the pulp and results in pulpal in lammation and necrosis (Packiri, 2017;Panchal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%